Yesus Hadiah Terindah: Pembinaan Iman Berdasarkan Lukas 2:10-11 di PPA ID0983 Anugrah Ngareanak, Singorojo, Kabupaten Kendal - Ragil Kristiawan; Eni Rombe (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
Abstract Faith building activities today are considered very important for the lives of youth and adolescents. In terms of spirituality, adolescents and young people often seek the meaning of life where this meaning will shape the existence of their lives. The need to bring the Savior together in the lives of youth and youth is also urgent. PPA ID0983 Anugrah Ngareanak understands this basic need very well. The solution that can be offered to introduce the Savior to PPA children is to hold a Faith Building in the context of PPA Christmas. The verse used for faith building is taken in Luke 2:10-11 which tells of shepherds who often experience discriminatory behavior from those around them. But in the frame of Christmas, God uses these shepherds to show that the most beautiful gift for the world has been born in the image of the Lord Jesus Christ as the Savior of the world. This activity was held on December 7, 2024 at STT Kristus Alfa Omega Semarang. PkM activities are divided into 2 classes, namely the Youth class for the 12-22 year age group and the teenager class for the 9-11 year age group. The provision method for the youth class uses interactive lectures, while the teenager class uses puppet stage props. The results of this faith development show positive things both from the enthusiasm of the participants and from the testimonies of the PPA mentors. Keywords: Christmas, The birth of Jesus, Salvation, Forgiveness, Luke 2:10-11 Abstrak Kegiatan pembinaan iman di masa kini dirasa sangat penting bagi kehidupan pemuda dan remaja. Dalam hal kerohanian, remaja dan pemuda sering mencari makna hidup dimana makna ini akan membentuk eksistensi kehidupan mereka. Kebutuhan untuk mempertemukan Juruselamat dalam kehidupan pemuda dan remaja juga dirasa sangat mendesak. PPA ID0983 Anugrah Ngareanak sangat mengerti akan kebutuhan mendasar ini. Solusi yang dapat ditawarkan untuk mengenalkan Juruselamat kepada anak-anak PPA adalah dengan mengadakan Pembinaan Iman dalam rangka Natal PPA. Ayat yang digunakan untuk pembinaan iman terambil dalam Lukas 2:10-11 yang mengisahkan para gembala yang sering mengalami perilaku diskriminatif dari orang-orang disekitarnya. Namun dalam bingkai natal, Allah memakai para gembala ini untuk menunjukkan bahwa hadiah terindah bagi dunia telah lahir dalam rupa Tuhan Yesus Kristus sebagai Juruselamat dunia. Kegiatan ini dilaksanakan pada tanggal 7 Desember 2024 di STT Kristus Alfa Omega Semarang. Kegiatan PkM dibagi menjadi 2 kelas yaitu kelas Pemuda untuk kelompok usia 12-22 tahun dan kelas remaja untuk kelompok usia 9-11 tahun. Metode pembekalan untuk kelas pemuda menggunakan ceramah interaktif, sedangkan kelas remaja menggunakan alat peraga panggung boneka. Hasil dari pembinaan iman ini menunjukkan hal yang positif baik dari antusias peserta maupun dari testimoni pembina PPA. Kata kunci: Natal, Kelahiran Yesus, Keselamatan, Mengampuni, Lukas 2:10-11